Faktor yang mempengaruhi praktik perawatan kaki pada penderita diabetes mellitus di wilayah kerja Puskesmas Rejosari, Propinsi Riau - Vivia Yunita Putri; Rani Lisa Indra; Susi Erianti (Jurnal Cakrawala Promkes, 2020)
Diabetes mellitus (DM) can cause complications to various body systems. One complication that often happens is diabetic foot. Obedience in carrying out foot treatment has an essential role in the therapy management of the patient with DM. This treatment aims to find out behaviour factors related to foot treatment. This research is a correlation description with the cross-sectional approach, conducted on 100 respondents in Rejosari Health Center. The sampling technique used was purposive sampling. Data were analyzed by univariate and bivariate analysis. The research result obtained is that there is no relation between age, gender, and the duration of suffering from DM and result of foot treatment with each p-value of 0.200, 0.739, 0.876 and 0.156 (>0,05). There is a relationship between education, occupation, counselling, family support, knowledge and perception of foot treatment practice with each p-value of 0.019, 0.041, 0.008, 0.001, 0.040 and 0.006 (< 0.05). It is expected that Rejosari Health Center is more often to give counselling about foot treatment to prevent the occurrence of complications.